2022
DOI: 10.3390/biom12101402
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity Is Predicted by Spatiotemporal Firing Rate Patterns and Robust to In Vivo-like Variability

Abstract: Synaptic plasticity, the experience-induced change in connections between neurons, underlies learning and memory in the brain. Most of our understanding of synaptic plasticity derives from in vitro experiments with precisely repeated stimulus patterns; however, neurons exhibit significant variability in vivo during repeated experiences. Further, the spatial pattern of synaptic inputs to the dendritic tree influences synaptic plasticity, yet is not considered in most synaptic plasticity rules. Here, we investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…As small protrusions that form on dendrites, structural changes in dendritic spines of neurons are crucial in the implementation of synaptic plasticity, and for memory storage and neuronal connectivity 21 . Synaptic plasticity is influenced by the spatial pattern of synaptic inputs to the dendritic spines 47 . In vivo studies have shown that dendritic spines of the cortex in the VD mice were also impaired 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As small protrusions that form on dendrites, structural changes in dendritic spines of neurons are crucial in the implementation of synaptic plasticity, and for memory storage and neuronal connectivity 21 . Synaptic plasticity is influenced by the spatial pattern of synaptic inputs to the dendritic spines 47 . In vivo studies have shown that dendritic spines of the cortex in the VD mice were also impaired 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium dynamics are extremely predictive of the change in synaptic weight. Calcium dynamics are affected by local synaptic activity and depolarization [ 85 ]. Voltage-dependent calcium channels that are activated by back-propagating action potentials lead to the enhancement of [Ca 2+ ] in , even in non-active dendrites [ 13 ] that can support backpropagation and the rate of firing [ 86 , 87 ].…”
Section: The Direction Of Plastic Changes: Ltp or Ltd Plasticitymentioning
confidence: 99%
“…7 This observed behavior is reminiscent of capacitive energy harvesting 9 from self-powered nanogenerators 10 and the movement of biomolecules that occurs during LTP at biological synapses. 11 Importantly, the presence of LTP in a pure lipid bilayer suggests that the specific capacitance, C m , of a biological membrane may not be a "biological" constant. 12 Here, we describe the molecular mechanisms responsible for LTP generation in a lipid bilayer induced by electrical stimulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Scott et al attributed this emergent LTP behavior to a combination of molecular and mesoscopic structural changes to the zwitterionic phosphatidylcholine (PC) lipid headgroups, the dielectric properties of the lipid bilayer, and the asymmetric buildup of charges across the lipid bilayer . This observed behavior is reminiscent of capacitive energy harvesting from self-powered nanogenerators and the movement of biomolecules that occurs during LTP at biological synapses . Importantly, the presence of LTP in a pure lipid bilayer suggests that the specific capacitance, C m , of a biological membrane may not be a “biological” constant …”
Section: Introductionmentioning
confidence: 99%